IMPACT OF BUERGER ALLEN EXERCISE ON ANKLE BRACHIAL INDEX IN TYPE II DIABETES MELLITUS PATIENTS - Permatasari, Eka Diana; Rakhman, Arif; Widodo, Yessy Pramita; Setyaningrum, Ikawati; Hidayat, Firman (Jurnal Keperawatan, 2025)
Type II Diabetes Mellitus (T2DM) carries a high risk of long-term complications, such as blood vessel damage from the buildup of glucose in the bloodstream . The incidence of T2DM complications, such as neuropathy and Peripheral Artery Disease (PAD), is notably high. These issues are often linked to low physical activity, as indicated by abnormal Ankle Brachial Index (ABI). One physical exercise for T2DM patients that can be done actively is the Buerger Allen Exercise (BAE). This study aims to analyze the effect of BAE on ABI values in T2DM patients. The study used a pre-experimental design with post-test only control group. Sampling was conducted through total sampling, with 20 participants in the intervention group and 20 in the control group. Data were collected by measuring the ABI values of the intervention group after on session of BAE for 20 minutes, and comparing them with the control group. The data were analyzed using the Mann-Whitney U test because of the non-normal distribution. The findings revealed a significant impact of BAE on ABI values in T2DM patients (p-value 0.003 < 0.05). The average ABI value post-BAE intervention in the treatment group was 0.79 (mild obstruction), while the control group had an average of 0.69 (moderate obstruction). The BAE physical exercise improves blood flow through muscle contractions and gravity, which increases peripheral perfusion, as demonstrated by the improvement in ABI values. The findings suggest that BAE can be implemented as a routine physical activity program for people with T2DM.